ANALISIS USAHATANI JAMUR TIRAM PUTIH (Pleurotusostreatus) DI KELURAHAN SIMPANG BARU KECAMATAN TAMPAN KOTA PEKANBARU - Retno Dewi Shintia; Amalia Amalia (Jurnal Ilmiah Pertanian, 2017)
This study aims to (1) analyze costs and farm income oyster mushroom in the village of Simpang Baru subdistrict Tampan Pekanbaru, (2) analyzing the viability of farming oyster mushroom in the village of Simpang New District of Pekanbaru, (3) Analyze Break Even Point (BEP ) white oyster mushroom business in the village new intersections Handsome District of the city of Pekanbaru. The sampling technique using census method. The results showed that during the production process (4 months) from 5000 baglog oyster mushrooms can produce immediate of 1200 kg, with a selling price at farmer level Rp. 30,000 / Kg. Total gross revenue for Rp.36.000.000, total production cost of Rp. 17,604,912. and net income of Rp. 18,395,088. BEP value sales of Rp. 5,668,708 and BEP unit amounted to 189.88 Kg. BCR value of 0.24 so that it can be concluded that the oyster mushroom farm in the village of Simpang Baru Subdistrict Tampan Pekanbaru City deserves to be continued